2020
DOI: 10.1108/ejm-11-2018-0772
|View full text |Cite
|
Sign up to set email alerts
|

How much firms “give” to CSR vs how much they “gain” from it: inequity perceptions and their implications for CSR authenticity

Abstract: Purpose The purpose of this study is to answer the call for additional detailed research on factors that influence corporate social responsibility (CSR) authenticity by examining how the former is affected by the commonly reported CSR spending allocations expressed as percentages of annual profits. It integrates equity and attribution theories to propose a new construct of inequity perceptions to explain how CSR spending allocations influence CSR authenticity. Inequity perceptions form from smaller allocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Therefore, it is critical to investigate the role of authentic CSR activities to maximize their effectiveness (Joo et al , 2019). Many researchers advocated that research on CSR authenticity is scant (Afzali and Kim, 2021; Fatma and Khan, 2022; Tarabashkina et al , 2020; Taylor, 2021), except for a few contributions. For example, Alhouti et al (2016) discovered a negative association between CSR authenticity and boycott response and recognized a positive association between CSR authenticity and purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to investigate the role of authentic CSR activities to maximize their effectiveness (Joo et al , 2019). Many researchers advocated that research on CSR authenticity is scant (Afzali and Kim, 2021; Fatma and Khan, 2022; Tarabashkina et al , 2020; Taylor, 2021), except for a few contributions. For example, Alhouti et al (2016) discovered a negative association between CSR authenticity and boycott response and recognized a positive association between CSR authenticity and purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…This is because when a plethora of brands offer the same or similar services, customers largely consider other factors when making purchase decisions; sincerity, heritage, and the commitment to quality (i.e., dimensions of BA) being among those most important (Grayson & Martinec, 2004). To form their perceptions of a brand’s authenticity, customers rely on multiple cues among which CSR endeavors are a key cue (Tarabashkina et al, 2020). However, although there is an emerging research stream studying the authenticity of CSR endeavors (Alhouti et al, 2016; Joo et al, 2019; Mazutis & Slawinski, 2015), there remains scant research examining how CSR endeavors influence the brand’s authenticity.…”
mentioning
confidence: 99%
“…Some studies have identified perceptual differences between 'large firms' and 'small firms,' and, at the same time, determine that the 'large firm' concept is sufficiently descriptive, with a meaning that is common and homogeneous among individuals (Green & Peloza, 2014). Tarabashkina, Quester, and Tarabashkina (2020) defend a similar approach that analyzes how a firm's size can bias consumer's inferences of inequity in CSR giving and its implications for CSR authenticity. In their work, they compare large firms and small firms and conclude that perceptions of inequity increase, and, therefore, that there are lower inferences of authenticity, when a large firm makes small contributions.…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 99%